1968
DOI: 10.1172/jci105888
|View full text |Cite
|
Sign up to set email alerts
|

Control of fluid absorption in the renal proximal tubule

Abstract: A B S T R A C T Glomerulotubular balance was investigated in isolated, perfused rabbit proximal tubules in vitro in order to evaluate some of the mechanisms proposed to account for the proportionate relationship between glomerular filtration rate and fluid absorption generally observed in vivo. The rate of fluid transport from lumen to bath in proximal convoluted tubules in vitro was approximately equal to the estimated normal rate in vivo. The absorption rate in proximal straight tubules however was approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1
2

Year Published

1969
1969
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 24 publications
7
97
1
2
Order By: Relevance
“…Burg and Orloff (20) had observed that in rabbit proximal tubule a 3-fold increase in perfusion rate produced a 37% increase in volume reabsorption, which was not statistically significant (Table 2 in ref. 20). However, this finding occurred in association with a 41% increase in tubule diameter.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Burg and Orloff (20) had observed that in rabbit proximal tubule a 3-fold increase in perfusion rate produced a 37% increase in volume reabsorption, which was not statistically significant (Table 2 in ref. 20). However, this finding occurred in association with a 41% increase in tubule diameter.…”
Section: Discussionmentioning
confidence: 80%
“…Accordingly, 3 H-inulin was added to the luminal perfusate as a volume marker, and fluid reabsorption was calculated by 3 H-inulin-concentration changes between the original and collected fluid (20). First, the flow-dependent proximal tubule transport was examined under the control condition in individual tubules.…”
Section: Resultsmentioning
confidence: 99%
“…to a large extent, inferential evidence, it has been widely held until recently that the cross-sectional area of the lumen of the proximal tubule is the principal determinant of the rate of sodium reabsorption by this segment (19)(20)(21)(22). More recent studies in the rat (11,23) and rabbit (24) have provided information that strongly opposes this interpretation. In these studies despite marked increases in calculated and measured values for tubule radius produced by elevation of ureteral pressure, renal venous occlusion and dilatation of isolated perfused proximal tubules, respectively, far less than proportionate increases, and often reductions in absolute reabsorptive rate were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated intact tubules absorb salt and water by active transport at the 280C temperature employed in these experiments. We assumed that the rate of active transport was unaffected by changes in tubular geometry (9). Hydraulic conductivity was calculated from the change in transmembrane flow occurring in response to a change in applied hydrostatic pressure.…”
Section: Methodsmentioning
confidence: 99%